Violence and social orders a conceptual framework for interpreting recorded human history - North, Douglass Cecil 1920-2015; Wallis, John Joseph 1952-; Weingast, Barry R. 1952- (Cambridge Univ. Press, 2013)
All societies must deal with the possibility of violence, and they do so in different ways. This study integrates the problem of violence into a larger social science and historical framework, showing how economic and political behavior are closely linked.
Originally published: 2009. - "With a new preface and afterword by the authors"--Cover. - Includes bibliographical references (pages 283-305) and index
Includes bibliographical references and index
Keywords: Geschichte; Gewalt; Politik; Politische Gewalt; Soziale Kontrolle; Soziale Werte; Wirtschaftstheorie; Violence -- Economic aspects -- History; State, The -- History; Social control -- History; Sozialordnung; Gesellschaft